Effect of whole-body vibration on lower-limb EMG activity in subjects with and without spinal cord injury. (September 2014) - Alizadeh-Meghrazi, Milad; Masani, Kei; Zariffa, José; Sayenko, Dimitry G.; Popovic, Milos R.; Craven, B. Catharine
<x content-type="archive" xml:space="preserve">Abstract</x> Objective Traumatic spinal cord injury (SCI) results in substantial reductions in lower extremity muscle mass and bone mineral density below the level of the lesion. Whole-body vibration (WBV) has been proposed as a means of counteracting or treating musculoskeletal degradation after chronic motor complete SCI. To ascertain how WBV might be used to augment muscle and bone mass, we investigated whether WBV could evoke lower extremity electromyography (EMG) activity in able-bodied individuals and individuals with SCI, and which vibration parameters produced the largest magnitude of effect. Methods Ten male subjects participated in the study, six able-bodied and four with chronic SCI. Two different manufacturers' vibration platforms (WAVE® and Juvent™) were evaluated. The effects of vibration amplitude (0.2, 0.6 or 1.2 mm), vibration frequency (25, 35, or 45 Hz), and subject posture (knee angle of 140°, 160°, or 180°) on lower extremity EMG activation were determined (not all combinations of parameters were possible on both platforms). A novel signal processing technique was proposed to estimate the power of the EMG waveform while minimizing interference and artifacts from the plate vibration. Results WBV can elicit EMG activity among subjects with chronic SCI, if appropriate vibration parameters are employed. The amplitude of vibration had the greatest influence on EMG activation, while the frequency of vibration had lesser but statistically significant impact on the measured lower extremity EMG activity. Conclusion These findings suggest that WBV with appropriate parameters may constitute a promising intervention to treat musculoskeletal degradation after chronic SCI.